2022
DOI: 10.3389/fpsyg.2022.939044
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment in third culture kids: A systematic review of literature

Abstract: Third Culture Kids (TCKs) are children of expatriates who live in a culture other than their country of nationality or their parent's country of nationality for a significant part of their childhood. Past research has indicated that adjustment is a key factor in the success of global mobility. However, current research in the area of TCK adjustment is lacking. This systematic review aims to present and summarize all available published scientific data on the adjustment of internationally mobile children and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The datasets presented in this study can be found in online repositories. The names of the repository/repositories and accession number(s) can be found at: Jones et al (2022) . Data set – Stress, Mental Health and Sociocultural Adjustment in Third Culture Kids: The Mediating Roles of Resilience and Family Functioning [Data set], Zenodo, https://doi.org/10.5281/zenodo.7304328 .…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The datasets presented in this study can be found in online repositories. The names of the repository/repositories and accession number(s) can be found at: Jones et al (2022) . Data set – Stress, Mental Health and Sociocultural Adjustment in Third Culture Kids: The Mediating Roles of Resilience and Family Functioning [Data set], Zenodo, https://doi.org/10.5281/zenodo.7304328 .…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The datasets presented in this study can be found in online repositories. The names of the repository/repositories and accession number(s) can be found at: Jones et al (2022)…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Living out the lattermost value has never been simple: growing up in the dominant U.S. culture by day and my parents’ Arab culture by night (a term I would later learn to be known as being a “third-culture kid” 1 ), much of my childhood was spent trying to establish my own sense of belonging and self-identity. Participating in “normal kid” activities such as dressing up for Halloween, going to the prom, and sleepovers with my American friends was typically perceived as a threat to my “Arab-ness” and therefore discouraged by my family.…”
mentioning
confidence: 99%